Evolusi Pasar Pemikiran Al-Ghazali Analisis Transaksi Elektronik (E-Commerce) - Zakiyyah Ilma Ahmad; Sirajul Arifin (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2021)
The purpose of this study is to analyze the evolution of the market from the time of the Prophet until the market is known as e-commerce, the meeting between sellers and buyers in an electronic transaction. By examining Al-Ghazali's thoughts regarding the evolution of the market, in which it still upholds Islamic ethics to conform to Islamic principles. This study uses a literature study instrument which is carried out by collecting data information related to buying and selling practices in e-commerce. The development of marketing evolution is associated with the evolution of the market of Al-Ghazali's thinking. When the market becomes e-commerce, experiencing very rapid development, there is a behavior of activity in the market, various kinds of market evolution, something natural will be perfect if it continues to use sharia principles